Whole genome analysis of Helicobacter pylori - Gunaletchumy, S.P.; Mason, J.N.; Saidin, A.; Teh, X.S.; Ramli, N.S.K.; Khosravi, Y.; Loke, M.F.; Mitchell, H.M.; Goh, K.L.; Vadivelu, J. (2012)
The human gastric microbiota may be more complex than originally thought and Helicobacter pulori may not be only microorganism found in the stomach. other bacteria that have been isolated from gastric biopsies include Streptococcus and Lactobacillus species.